64. FOOT SELF – CARE PRACTICE AMONG DIABETIC PATIENTS ATTENDING AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Identify rate of foot self – care practice among diabetic patients attending at Thong Nhat hospital.Subject and method: cross – sectional study with sample size is 95 patients. Using questionnaire to observe and interview participants.Results: There are 38,9% participants practice self – check their foot everday, 100% patients use prescription drug. There are 35,8% patients practice correctly foot self – care.Conclusion: clinical nurses need to guide foot self – care practice among diabetic.
Keywords: foot self – care; diabetic type 2